Evaluation of the Strep B OIA Test Compared to Standard Culture Methods for Detection of Group B Streptococci - J. Y. Song; L. L. Lin; S. Shott; N. Kimber; J. Tangora; A. Cohen; A. Wells; M. Maezes; A. Aroutcheva; S. Faro (Hindawi Limited, 1999)
Objective: This study evaluated the accuracy of the commercial product Strep B OIA (optical immunoassay) compared to the standard agar and broth culture methods for detecting vaginal colonization with group B streptococcus (GBS).